Production of plasmid-encoding NDM-1 in clinical Raoultella ornithinolytica and Leclercia adecarboxylata from China - Sun, Fengjun; Yin, Zhe; Feng, Jiao; Qiu, Yefeng; Zhang, Defu; Luo, Wenbo; Yang, Huiying; Yang, Wenhui; Wang, Jie; Chen, Weijun; Xia, Peiyuan; Zhou, Dongsheng (Frontiers in Microbiology, 2015)
Raoultella ornithinolytica YNKP001 and Leclercia adecarboxylata P10164, which harbor conjugative plasmids pYNKP001-NDM and pP10164-NDM, respectively, were isolated from two different Chinese patients, and their complete nucleotide sequences were determined. Production of NDM-1 enzyme by these plasmids accounts for the carbapenem resistance of these two strains. This is the first report of blaNDM in L. adecarboxylata and third report of this gene in R. ornithinolytica. pYNKP001-NDM is very similar to the IncN2 NDM-1-encoding plasmids pTR3, pNDM-ECS01, and p271A, whereas pP10164-NDM is similar to the IncFIIYblaNDM-1-carrying plasmid pKOX_NDM1. The blaNDM-1 genes of pYNKP001-NDM and pP10164-NDM are embedded in Tn125-like elements, which represent two distinct truncated versions of the NDM-1-encoding Tn125 prototype observed in pNDM-BJ01. Flanking of these two Tn125-like elements by miniature inverted repeat element (MITE) or its remnant indicates that MITE facilitates transposition and mobilization of blaNDM-1 gene contexts.